Enhancing the Néel temperature in 3d/5d R2NiIrO6 (R=La, Pr and Nd) double perovskites by reducing the R3+ ionic radii. (1st April 2021) - Kayser, P.; Muñoz, A.; Martínez, J.L.; Fauth, F.; Fernández-Díaz, M.T.; Alonso, J.A.
Abstract: Double perovskites containing Ir 4+ were synthesised by a citrate technique, followed by an annealing treatment in air at 1100 °C. The crystal structure of the three compounds, with formula R2 NiIrO6 (R= La, Pr and Nd), were determined using a combined refinement against neutron powder diffraction (NPD) and synchrotron x-ray powder diffraction (SXRPD) data sets. At room temperature, all the samples were indexed in the space group P21 /n and the monoclinic symmetry remains in the 300 to 1273 K temperature range. Magnetization measurements suggest competitive antiferromagnetic and ferromagnetic interactions, with an unexpected increment of the ordering temperature (TN ) along the series. The magnetic structures of all the samples were defined with the propagation vector k = 0; the Ni 2+ and Ir 4+ moment arrangement, different for each compound, shows a strong dependence on the nature of the rare-earth ion. Graphical abstract: Image, graphical abstract